Gender-Specific Risk of Central Compartment Lymph Node Metastasis in Papillary Thyroid Carcinoma - Yushi Sun; Hongjun Lv; Shaoqiang Zhang; Yanxia Bai; Bingyin Shi (International Journal of Endocrinology)
Our aim was to evaluate the impact of gender on the predictive factors of central compartment lymph node metastasis (CLNM) in papillary thyroid carcinoma (PTC). A retrospective study of 590 patients treated for PTC was performed. Univariate and multivariate analyses showed that gender (female; P=0.001), age (≥45 y; P<0.001), tumor size (>1 cm; P<0.001), and multifocality (P=0.004) were independent predictive factors of CLNM in PTC patients. Patients were divided into male group (n=152) and female group (n=438). Age (≥45 y; P=0.001), T4 (P=0.006) and multifocality (P=0.024) were independent predictive risk factors of CLNM in male patients. As for female patients, age (≥45 y; P<0.001), tumor size (>1 cm; P<0.001), multifocality (P=0.002), and microcalcification (P=0.027) were independently correlated with CLNM. The sensitivity of the multivariate model for predicting CLNM in male patients was 64.9%, specificity was 82.9%, and area under the ROC curve (AUC) was 0.764. As for female patients, the sensitivity was 55.7%, specificity was 77.9%, and AUC was 0.73. This study showed that the predictive factors of CLNM indeed varied according to gender. To have a more accurate evaluation of CLNM, different predictive systems should be used for male and female patients.